Integrated analysis of electrical stimulation effects on Pseudomonas aeruginosa PAO1 inoculated denitrifying community: targeted and untargeted metabolomic analysis of phenazine biosynthesis and quorum sensing - Wu, Li; Liu, Yong; Deng, Jianping; Gui, Shuanglin; Nie, Hanbing (Frontiers in Microbiology, 2025)
This study investigates how 0.8 V applied voltage modulates phenazine biosynthesis, quorum sensing (QS), and microbial interactions in Pseudomonas aeruginosa PAO1-inoculated microbial electrolysis cell (MEC) reactors. Voltage stimulation significantly enhanced phenazine derivatives (PYO: 8.65-fold; 1-OH-PHZ: 14.98-fold) and QS signals (C4-HSL: 2.88-fold; 3-OXO-C12-HSL: 2.21-fold), correlating with upregulated biosynthetic genes (phzG: 14.8-fold; rhlI: 15.2-fold). Electrical stimulation amplified QS cross-regulation, reinforcing Las-mediated positive feedback on Rhl/PQS systems while attenuating Rhl’s inhibition of PQS. Untargeted metabolomic analysis demonstrated significant alterations in bacterial metabolic activity under electrical stimulation, identifying 140 differential metabolites. Among these, indole, a signaling molecule with QS-like functionality, exhibited the highest VIP score as an upregulated metabolite, and another indole derivative, brassicanal A, was also elevated. KEGG pathway enrichment analysis highlighted that these metabolites were primarily associated with amino acid metabolism and transport, while anthranilic acid and L-tryptophan—key metabolites linked to both indole-related pathways and phenazine biosynthesis—were also identified. Correlation analysis between differential metabolites with microbial communities confirmed that Delftia and Burkholderiales were strongly associated with phenazine biosynthesis and QS activity in P. aeruginosa PAO1. These findings highlight voltage as a key driver of metabolic rewiring and microbial niche partitioning, optimizing MEC reactor performance for wastewater treatment. This work provides foundational insights into electro-stimulated biofilm engineering through targeted QS and metabolic pathway regulation.